Discipline-Specific Perspectives on Caring for Babies with Trisomy 13 or 18 in the Neonatal Intensive Care Unit - Torbert, Nicholas; Neumann, Marie; Birge, Nicole; Perkins, Donnetta; Ehrhardt, Elizabeth; Weaver, Meaghann S. (American Journal of Perinatology, 2020)
Objective Care offerings vary across medical settings and between families for babies with trisomy 13 or 18. The purpose of this qualitative descriptive study was to explore nurse, advanced practice practitioner, and neonatologist perspectives on care for babies with trisomy 13 or 18 in the intensive care unit.Study Design Voice-recorded qualitative interviews occurred with 64 participants (41 bedside nurses, 14 advance practice practitioners, and 9 neonatologists) from two neonatal intensive care units (NICU) in the midwestern United States. Consolidated Criteria for Reporting Qualitative Research guidelines were followed. Content analyses occurred utilizing MAXQDA (VERBI Software, 2020).Results Over half of NICU staff perceived care for babies with trisomy 13 or 18 as different from care for other babies with critical chronic illness. Qualitative themes included internal conflict, variable presentation and prognosis, grappling with uncertainty, family experiences, and provision of meaningful care. Neonatologists emphasized the variability of presentation and prognosis, while nurses emphasized provision of meaningful care. Phrases “hard/difficult” were spoken 31 times; primarily describing the comorbidities, complexities, and prognostic uncertainty.Conclusion Care for babies with these genetic diagnoses reveals need for a shared dialogue not only with families but also across staff disciplines. While perspectives differ, participants depicted striving to offer compassionate, family-centered care while also balancing biomedical uncertainty about interventions for children with trisomy 13 and 18.Key Points
Keywords: trisomy 13; trisomy 18; communication; interdisciplinary; palliative care